A Study on Development Disparities in Papua Tengah Province: Assessing Per Capita Income Disparities and Recommending Equitable Development Strategies - Mesak Iek; Marsi Adi Purwadi; Pisi Bethania Titalessy (Journal of The Community Development in Asia, 2024)
This research is a study of development disparities between regions in Papua Tengah Province which aims to (1) know and analyze disparities in per capita income between regions in Papua Tengah Province; and (2) analyze and prepare recommendations regarding efforts to overcome development disparities between regions in Papua Tengah Province. Data and information gathered from various regions undergo processing and examination through quantitative and qualitative methods. These approaches encompass evaluating factors like per capita income, employment across sectors, savings rates, urbanization levels, literacy rates, life expectancy, infant mortality rates, along with offering policy suggestions based on research outcomes. The data utilized is sourced from governmental bodies like BPS, Bappeda, Dispenda, as well as non-governmental institutions such as Bank Indonesia. Research analysis involves growth assessment, disparity examination, and descriptive statistical analysis. The result shows that over the past decade (2013-2022),Â  there has been significant economic inequality among districts/cities within Papua Tengah Province region, indicating unequal economic growth across regions. Efforts that need to be made by Regency/City Governments in Papua Tengah Province are to improve the performance of community welfare aspects which are considered capable of driving equitable development in each region.